Transcriptome and Metabolome Analysis of Organic and Chemical Fertilizer Effects on Highland Barley Growth and Nutrient Utilization - Jiahui Yan; Hua Weng; Lu Hou; Qiang Yao; Tao He (Agronomy)
The rate of chemical fertilizers’ utilization by crops does not exceed 40%. Environmental pollution and resource waste caused by the excessive application of chemical fertilizers have led to increased interested in using organic fertilizers as replacements for chemical ones. The present study investigated the impact of the combined application of chemical and organic fertilizers on the growth and nutrient utilization efficiency of highland barley (Hordeum vulgare L.). Compared to the application of 100% chemical fertilizers (OFR0), the substitution of chemical fertilizer with 40% organic fertilizer (OFR40) resulted in a significant increase in root length by 4% and improved the nutrient absorption capacity. The crop yields at harvest were not diminished in the combined fertilizer group compared to the OFR0 treatment group, while simultaneously achieving a 60% reduction in chemical fertilizer application. However, a complete substitution with 100% organic fertilizer (OFR100) resulted in a lower yield. This suggests that appropriate proportions of organic fertilizer replacement can maintain yield by increasing root length and enhancing the crop’s nutrient absorption capacity. In order to elucidate the mechanisms by which organic fertilizer modulates crop growth and nutrient utilization efficiency, combined transcriptomic and metabolomic analysis revealed that as the concentration of organic fertilizer increased, the differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) shifted from secondary metabolite synthesis toward nitrogen metabolism. In addition, the gene expression and enzymatic activity of NR (nitrate reductase), GS (glutamine synthetase), and GOGAT (glutamine oxoglutarate aminotransferase) (key genes in the nitrogen metabolism pathways) were significantly enhanced in the OFR40 group. This study’s omics-based approach demonstrates that the combined use of chemical and organic fertilizers enhances nitrogen absorption and utilization through an increased expression of key genes and enzymatic activities within the nitrogen metabolic pathways. This synergistic effect not only maintains crop yields but also reduces the reliance on chemical fertilizers, offering a sustainable strategy for agricultural production.